2013
DOI: 10.1352/1934-9556-51.4.237
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Impressions of a Precepted Clinical Experience Caring for People With Disabilities

Abstract: There is evidence that early and frequent encounters with people with disabilities can improve medical students' knowledge, skills, and attitudes about disability. As part of a 4-year integrated curriculum in caring for patients with disabilities, third-year medical students (n = 144) in a Family Medicine clerkship participated in a day-long precepted clinical experience at a medical facility serving people with disabilities, predominantly developmental disabilities, where they met patients and worked with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…We also evaluated qualitative feedback by students about individual elements of the curriculum, which indicates that the curriculum did have a positive impact on students' experience working with people with disabilities. 34 We demonstrated that students in the intervention group tended to report more comfort in interacting with people with disabilities than did those in the control, supporting the hypothesis that increased exposure leads to increased comfort, and that a focused experience working with people with disabilities serves to increase comfort level more than just incidental exposure provided in routine training. 12,20 Students who experienced the curriculum were more likely to report feeling comfortable around someone with a disability (with or without someone accompanying the patient), and were more likely to acknowledge that people with disabilities are as happy as those as people without disabilities.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We also evaluated qualitative feedback by students about individual elements of the curriculum, which indicates that the curriculum did have a positive impact on students' experience working with people with disabilities. 34 We demonstrated that students in the intervention group tended to report more comfort in interacting with people with disabilities than did those in the control, supporting the hypothesis that increased exposure leads to increased comfort, and that a focused experience working with people with disabilities serves to increase comfort level more than just incidental exposure provided in routine training. 12,20 Students who experienced the curriculum were more likely to report feeling comfortable around someone with a disability (with or without someone accompanying the patient), and were more likely to acknowledge that people with disabilities are as happy as those as people without disabilities.…”
Section: Discussionsupporting
confidence: 67%
“…Although this allowed the students to acquire focused experience working with people with disabilities, it may have also served to reinforce the perception that people with disabilities require and/or demand special treatment. 34 Wright noted that in settings which show a person with disability functioning in terms of his or her capabilities (i.e. equal status), attitude measures are likely to become more favorable than in settings that highlight the person's disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found that providing specific training to medical students as well as opportunities for them to encounter patients with disabilities yields benefits in terms of improving student's attitudes and comfort level regarding people with disabilities and increasing their knowledge and skills in providing care to these patients (Brown et al 2010;Karl et al 2013;Long-Bellil et al 2011). Few medical schools or residency programs currently offer these kinds of training experiences although this has begun to change (Graham et al 2009;Moroz et al 2010;Symons et al 2009) and research is being conducted to better assess the efficacy of these efforts (Symons et al 2012;Lam et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Research suggesting improved attitudes: qualitative work Karl et al (2013) qualitatively examined medical students' written responses to an Internet survey on their reflections about a clinical experience, in which they met patients with developmental disabilities and worked with professionals in this area. A survey was used to avoid interviewer and response bias; however, the author did not describe consideration of the relationship between the researcher and participants as recommended by CASP (2013), and interviews or focus groups may have produced richer data.…”
Section: Research Suggesting Improved Attitudes: Generic Measuresmentioning
confidence: 99%